(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In the article, the opinion on the separation of four functions in management theory: planning, organization, motivation and control functions is presented. In such cases, a situational approach is used to determine the functional composition of management activities. As a result of the popularization of the situational approach in management, experts have distinguished other functions of management: goal setting, communication, and motivation.